Complete mitochondrial genome of Formosania chenyiyui (Osteichthyes: Gastromyzontidae). Issue 1 (2nd January 2019) - Wan, Hong; Song, Xiaojing; Tang, Wenqiao
Abstract: The Formosania is only distributed in a narrow area in Southeast China, and differentiation of the species of this genus may be helpful in understanding the formation process of the water system on both sides of the Taiwan Strait. The complete mitochondrial genome of Formosania chenyiyui is sequenced in this paper. The results show that the full length of the complete mitochondrial genome is 16, 572 bp, comprising 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region. Overall base composition is 30.35% A, 26.68% T, 15.86% G, and 27.11% C. The result of phylogenetic analysis suggests that F. chenyiyui is close to that of F. lacustre and Vanmanenia stenosoma, and accords with the evolutionary viewpoint of Formosaniini group based on morphological characteristics.